Study of the English Autonomous Learning Situation of College Freshmen in the “Internet Plus” Era - Wang , Ying; Wang, Chao (Advances in Social Sciences Research Journal, 2019)
Combining “the Internet plus” technology with education makes it possible and convenient for learning to happen beyond the restraints of time and place. Following this new trend of autonomous learning, learners have obtained easier access to the learning resources they need. Freshmen are clearly an indispensable group who benefit from it. Based on the theory of multiple intelligences and constructivist learning theory, this thesis aims to discover the current status of freshmen’s autonomous learning in the internet plus era through questionnaires and interviews, explore the impact of learning tools and learning environments supported by internet plus technology on students’ autonomous learning ability and effectiveness, and provide some corresponding advice for college English learning and teaching practice. A questionnaire survey followed by a face-to-face interview is employed in this thesis. The researcher randomly selected 460 freshmen with an English proficiency of level B (the intermediate level based on the Entrance Level Test hosted by BIPT) as subjects, issued relevant questionnaires online, and analyzed the final data via SPSS 20. Results show that freshmen at BIPT do have the awareness of autonomous learning with the help of various platforms online and apps on smart phones, but they have problems in making a long-term study plan, and following the plan regularly. They do have the motivation to improve their English competency through autonomous learning in the “Internet-plus” environment, but they have difficulty in information processing and resources acquisition. There is a correlation between college freshmen’s autonomous learning ability and their English academic achievements. Freshmen with better abilities of autonomous learning tend to get higher scores in the English test. It is strongly suggested that students should be more self-disciplined in terms of self-planning and self-supervising. In order to guarantee the effectiveness of autonomous learning, it is necessary for teachers to provide specific guidance, such as helping students make feasible study plans and regularly checking their implementation of the plans. Due to the limitation of time and resources, the design of the questionnaire only focuses on certain aspects of autonomous learning, and the quantity of the sampling is not large enough. The author hopes that more researches would be done to further explore the nature of autonomous learning in the “Internet plus” era and make it a booster for education and self-development.